Epiplakin modifies the motility of the HeLa cells and accumulates at the outer surfaces of 3‐D cell clusters. Issue 4 (11th February 2013) - Shimada, Hiromitsu; Nambu‐Niibori, Akiko; Wilson‐Morifuji, Masayo; Mizuguchi, Souhei; Araki, Norie; Sumiyoshi, Hideaki; Sato, Mitsuru; Mezaki, Yoshihiro; Senoo, Haruki; Ishikawa, Kazushi; Hatano, Yutaka; Okamoto, Osamu; et al.
Abstract Elimination of epiplakin (EPPK) by gene targeting in mice results in acceleration of keratinocyte migration during wound healing, suggesting that epithelial cellular EPPK may be important for the regulation of cellular motility. To study the function of EPPK, we developed EPPK knock‐down (KD) and EPPK‐overexpressing HeLa cells and analyzed cellular phenotypes and motility by fluorescence/differential interference contrast time‐lapse microscopy and immunolocalization of actin and vimentin. Cellular motility of EPPK‐KD cells was significantly elevated, but that of EPPK‐overexpressing cells was obviously depressed. Many spike‐like projections were observed on EPPK‐KD cells, with fewer such structures on overexpressing cells. By contrast, in EPPK‐KD cells, expression of E‐cadherin was unchanged but vimentin fibers were thinner and sparser than in controls, and they were more concentrated at the peri‐nucleus, as observed in migrating keratinocytes at wound edges in EPPK−/− mice. In Matrigel 3‐D cultures, EPPK co‐localized on the outer surface of cell clusters with zonula occludens‐1 (ZO‐1), a marker of tight junctions. Our results suggest that EPPK is associated with the machinery for cellular motility and contributes to tissue architecture via the rearrangement of intermediate filaments.